The Small Claims Court An Argumentative Instructional Alternative - O'Rourke, Sean Patrick ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1981)
This paper explores the small claims court as an alternative forum for the instruction of argumentation and suggests a possible format of a course utilizing such a concept. The first section of the paper offers a short history of the small claims court. The second section contains a course syllabus outlining the format of an argumentation course built around the small claims system. The third section is an analysis of the application of certain aspects of argumentation theory in the small claims setting. Examples of assignments and review questions are appended. (RL)
ERIC Note: Paper presented at the Annual Meeting of the Western Speech Communication Association (San Jose, CA, February 14-16, 1981).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Court Doctrine; Court Role; Courts; Evaluation Criteria; Higher Education; Legal Education; Persuasive Discourse; Speech Communication; Speech Curriculum; Information Analyses; Guides, Classroom -- Teacher; Speeches/Meeting Papers